Tomato and tilapia yield, quality and safety in an intensive aquaponic system /Produtividade, qualidade e seguranca de tomate e tilapia em sistema aquaponico intensivo - De leon-Ramirez, Jesus J; Garcia-Trejo, Juan F; Sosa-Ferreyra, Carlos F; Felix-Cuencas, Leticia; Lopez-Tejeida, Samuel (Revista brasileira de engenharia agrícola e ambiental, 2025)
In aquaponics, a limitation in productive performance is the concentration of nutrients for plant development. So, the intensity of fish in the culture could be an internal variant that favors the presence of nutrients, thus avoiding their external supply. Therefore, the aim was to determine the effect of intensive fish density during its three biological stages (fingerling, juvenile, and adult) on the yield, quality, and safety of tomato (Solatium lycopersicum) and tilapia (Oreochromis niloticus) in an aquaponic system. The study was conducted using a randomized block design, having as an experimental unit an intensive aquaponic system and as a control, an aquaculture module and a hydroponic module, each with three replications. The response variables for plant yield were dry weight, relative growth rate, crop growth rate, survival rate, and production per plant, and for fish, there were growth rate, feed conversion factor, protein efficiency ratio, and survival rate. For fruit quality, the variables were pH, total soluble solids (TSS), titratable acidity (TA), TSS/TA ratio, and lycopene content; for fillet quality, the following were considered: percentage of protein, lipids, ash, and nitrogen-free extract. Finally, in the safety evaluation of both products, the variables were the presence of total coliforms, Salmonella, and Escherichia coli. Intensive fish density (40 kg/[m.sup.3]) significantly improves tilapia biomass and fillet quality, while tomato yield remains comparable to that of hydroponics, with some quality variables even higher, without showing significant differences in the microbiological safety of the fillet or the fruit. Key words: Oreochromis niloticus, Solanum lycopersicum, aquaponic systems, productive performance Em aquaponia, uma limitacao no desempenho produtivo e a concentracao de nutrientes disponiveis para o desenvolvimento das plantas. Assim, a densidade de peixes pode atuar como uma variavel interna que favorece a disponibilidade de nutrientes, reduzindo a necessidade de suplementacao externa. Assim, o objetivo deste estudo foi determinar o efeito da densidade intensiva de peixes durante tres estagios biologicos (alevino, juvenil e adulto) sobre a produtividade, qualidade e seguranca do tomate (Solanum lycopersicum) e da tilapia (Oreochromis niloticus) em sistema aquaponico. O experimento foi conduzido em um delineamento em blocos casualizados, tendo como unidade experimental um sistema aquaponico intensivo e, como controles, um modulo de aquicultura e um modulo hidroponico, com tres repeticoes. As variaveis-resposta avaliadas para a produtividade vegetal foram: massa seca, taxa de crescimento relativo, taxa de crescimento da cultura, taxa de sobrevivencia e producao por planta. Para os peixes, foram analisadas: taxa de crescimento, fator de conversao alimentar, taxa de eficiencia proteica e de sobrevivencia. A qualidade dos frutos foi determinada atraves das variaveis: pH, solidos soluveis totais, acidez titulavel, razao SST/AT e teor de licopeno. Para a qualidade do file de tilapia, foram consideradas as porcentagens de proteina, lipidios, cinzas e extrato livre de nitrogenio. Por fim, a avaliacao da seguranca microbiologica dos produtos incluiu a presenca de coliformes totais, Salmonella spp. e Escherichia coli. A densidade intensiva de peixes (40 kg/[m.sup.3]) melhorou significativamente a biomassa e a qualidade do file de tilapia, enquanto a produtividade do tomate se manteve comparavel a da hidroponia, com algumas variaveis de qualidade superiores, sem diferencas significativas na seguranca microbiologica dos files ou dos frutos. Palavras-chave: Oreochromis niloticus, Solanum lycopersicum, sistemas aquaponicos, desempenho produtivo